2016
DOI: 10.1590/s1413-70542016000100009
|View full text |Cite
|
Sign up to set email alerts
|

Cheese bread enriched with biofortified cowpea flour

Abstract: The development and enrichment of food are of great importance not only for the industry but also to improve the population's nutrition, where you can create new products or optimize existing ones. The consumption of fortified products in the diet is an option for the control of deficiency diseases. This study aimed to develop enriched cheese bread with whole biofortified cowpea flour and evaluate their acceptance and chemical composition. Two formulations, F1 and F2, were prepared containing 5.6 and 8% of cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
1
10
2
6
Order By: Relevance
“…According to methodology adapted from Cavalcante et al (2016) for the preparation of cheese bread, the dry ingredients (sweet starch, FFC, parmesan cheese, and salt) were homogenized and then the remaining raw materials (milk, egg, and oil) were added to the mixture. The mass was homogenized and then shaped manually, so that the loaves could acquire a round shape.…”
Section: Preparation Of the Cheese Breadmentioning
confidence: 99%
“…According to methodology adapted from Cavalcante et al (2016) for the preparation of cheese bread, the dry ingredients (sweet starch, FFC, parmesan cheese, and salt) were homogenized and then the remaining raw materials (milk, egg, and oil) were added to the mixture. The mass was homogenized and then shaped manually, so that the loaves could acquire a round shape.…”
Section: Preparation Of the Cheese Breadmentioning
confidence: 99%
“…When these results were compared with our study results, only total energetic value and crude protein were higher, as amaranth flour was used in the CB formulation. Cavalcante et al (2016) studied CB using cowpea flour and found similar values for moisture (26.9 g 100 g -1 ), crude protein (10.6 g 100 g -1 ), total ash (2.9 g 100 g -1 ), and total energy (321.3 kcal).…”
Section: Proximal Compositionmentioning
confidence: 86%
“…Ayrıca, börülce gluten içermediğinden çölyak hastaları için üretilen glutensiz fırıncılık ürünlerinin zenginleştirilmesinde de rahatlıkla kullanılabilmektedir (Cavalcante et al, 2016).…”
Section: Ekmeğin Baklagil Ve Diğer Proteinli Gıdalar Ile Zenginleştirunclassified